Multiple gastric gastrointestinal stromal tumors treated by laparoscopic‐endoscopic cooperative surgery: A case report. Issue 4 (29th July 2016) - Maeda, Eri; Fujiwara, Masao; Suto, Hironobu; Asano, Eisuke; Kishino, Takayoshi; Yamamoto, Naoki; Akamoto, Shintaro; Okano, Keiichi; Kobara, Hideki; Mori, Hirohito; Masaki, Tsutomu; Suzuki, Yasuyuki
Abstract: The typical treatment of choice for gastrointestinal stromal tumors (GIST) is surgical resection. Here we report a case of three GIST lesions resected safely by laparoscopic‐endoscopic cooperative surgery (LECS). A 78‐year‐old woman was referred to our hospital for further treatment of an enlarging gastric submucosal tumor. Esophagogastroduodenoscopy and endoscopic ultrasonography revealed two gastric submucosal tumors. Endoscopic ultrasonography‐guided fine needle aspiration was subsequently performed. The patient underwent LECS in accordance with therapeutic guidelines for GIST. Assisted by a laparoscope and using three trocars, a full‐thickness resection was performed endoscopically for the 3‐cm lesion and its nearby submucosal tumor, which was newly detected intraoperatively. The other lesion was also resected with an autosuture device under laparoscopy. No intraoperative or postoperative complications were observed. In LECS, endoscopic observation and resection can minimize gastric deformation and preserve gastric function. To the best of our knowledge, this is the first case of LECS performed on multiple GIST.